ESENSI MANUSIA DALAM PRESPEKTIF FILSAFAT PENDIDIKAN ISLAM - Ahmad Fuadi (UIN Sumatera Utara Medan, 2016)
The Holy Quran has three terms are often referred to as a term for human beings, namely al-Insan al-Basyar and the sons of Adam. The third term, each having its own meaning. Man said al-Insan is viewed from the side of kediriannya as a thinking being, al-Basyar is showing the physical dimensions of the human being, while the sons of Adam are seen from the human lineage. Man was created comes with dimensions of jasmaniyah and ruhiyah, so with both dimensions this man can become the perfect creature surpasses other creatures. The advantages given to humans also demands the man for the task and function of its creation, either as a servant of God and as a khalifah fil ard. Islamic education task mempunnyai important enough in this case, namely, how to create a human being who is able to develop all potential so that human beings are able to execute his duties as both a servant of God and as the leader in the face of the Earth.Key Words: Human, The Essence Of The Philosophy Of Islamic Education.